EFEKTIVITAS PROGRAM BANTUAN SOSIAL RUMAH TIDAK LAYAK HUNI (BANSOS-RTLH) DI KOTA TEGAL TAHUN 2017 - Rahmawati - Zania; Puji - Astuti; Teguh - Yuwono (Journal of Politic and Government Studies, 2018)
The housing problem is one of the things that is getting more attention from the Government at various levels, from the central government to the local government. The main issues of housing and settlement problems are the increasing number of slums in various regions in Indonesia. The need for boards (shelter), clothing, and food is not directly proportional to the income and the knowledge of the community about a habitable home. The Uninhabitable House Social Assistance Program is a program implemented by the Tegal City Government for low-income people in order to have a decent home. this program in practice has been running quite well and effectively because it has reduced the number of uninhabitable houses in Tegal City and managed to repair the house through repair in some parts of the house such as roofs, floors and walls. This research contributed to Governance Science in policy formulation. Result and discussion: the effectiveness of the implementation of the Uninhabitable House Social Assistance program in Tegal City has been effective with a value of 2.67. Indicator of socialization and program understanding of 2.36. The target accuracy indicator is 3.37. The program objectives indicator is 2.56. The indicator of real change was 2.70 and the program monitoring indicator was 2.37. However, in the implementation, there are still obstacles such as aid funds that are still not enough to repair houses, unfulfilled conditions such as citizens who reject the assistance so that the implementation was hampered, the uneven distribution of budgets in each village or each house, time execution is too short so that the workmanship is less than maximum, and lack of socialization programs so that many residents who still do not understand about the program in detail.Conclusions and recommendations: The Uninhabitable House Social Assistance Program has been running quite effectively as evidenced by public opinion with value indicator is 2,67. Furthermore this program also has helped significantly reduce the number of slums ini Tegal city where within 2 years the number of uninhabittable house has been handled around 41% of the number of uninhabittable house registered in PBDT. Government and society have their respective responsibility to create welfare, therefore good cooperation between government and society is needed for the program that has been formulated by government can run effectively and can reach the purpose which have been determined. Keywords: effectiveness, The Uninhabitable House Social Assistance Program